ANALISIS PERBANDINGAN PENDAPATAN USAHATANI PADI (ORYZA SATIVA L) TANAM PINDAH DAN HAMBUR LANGSUNG - ANDI BESSE DAHLIANA; HASMIDAR HASMIDAR; SUNARSI SUNARSI (Universitas Mahasaraswati K. Mataram, 2023)
The results of field observations in Barebbo Sub-District, the majority of the people are rice business actors using the transplanting planting method and direct seed planting. with a land area of 405 ha which is divided into several strata of land area. Lowland rice farming income using transplanting method and direct seed planting as seen from the use of labor, seeds, costs and farmers' income. The purpose of this study was to find out the comparison of income from rice farming by transplanting parallel rows and direct scattering. This research was carried out for 3 months, from November to January 2022. The number of samples was 40 farmers with a distribution of 20 farmers using the horizontal transplanting system and 20 farmers using the direct scatter seed planting system using the Slovin formula. The technique of determining the sample using purposive sampling method while the research data uses primary data and secondary data. Data analysis used is a type of quantitative data in the form of income analysis. Based on the results of this study, the average income of farmers in transplanting transplanted rice farming is Rp. 25,593,000/ha with an R/C of 2.88, while the average income of farmers in direct scattering rice farming is Rp. 17,993,000/ha with an R /C 2.28 while the average income of farmers in transplanting transplanted rice farming is Rp.16,711,925/ha while the average income of farmers in direct scattering rice farming is Rp.10,484,050/ha.